Motivations for Entrepreneurship of Students in Vietnam - Đinh, Văn Toàn (2020)
Entrepreneurship, as an engine for economic growth, has drawn much attention in these recent decades worldwide. Numerous studies have examined factors affecting entrepreneurial attitudes and intention in a variety of geographical contexts. However, a few studies use Maslow’s hierarchy of needs theory as a theoretical background to explain the motivations for entrepreneurship. Therefore, this paper fills in the gap in the existing literature of motivations and entrepreneurship. A research model was adapted from related work to test the influence of deficiency-need motivations and growth-need motivation on the entrepreneurial intention of Vietnamese young people. Based on the data from a self-administered survey with 600 Vietnamese students, research results confirmed the positive relationship between entrepreneurial intention and deficiency needs, such as physiological needs, safety needs, and belongingness needs. More interestingly, gender plays a controlling role in the mentioned relationship between motivations and entrepreneurial intention. These findings suggest solutions for policymakers and universities to promote entrepreneurship among young people.